Low-shrinkage and high-resilience supercritical polyurethane foaming bead and preparation method thereof
By introducing benzene ring structure into the TPU soft segment and optimizing the polyester polyol synthesis method, combined with the carbon dioxide foaming process under the autoclave, the problem of insufficient skeleton strength after foaming of supercritical polyurethane foam beads is solved, and the low skeleton strength of supercritical polyurethane foaming beads is achieved The preparation of supercritical polyurethane foamed beads with shrinkage and high resilience improves the overall performance of the product.
Patent Information
- Application Number
- CN202411865795.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing supercritical polyurethane foamed beads have poor skeleton strength after foaming and pressure relief, which is prone to shriveling and surface wrinkles, and has a high shrinkage rate, which affects the product's rebound and structural stability.
The benzene ring structure is introduced into the TPU soft segment to optimize the synthesis method of polyester polyol. By adding dibasic acid and refined terephthalic acid separately, the glass transition temperature and polarity are improved, and combined with high pressure The carbon dioxide foaming process under the kettle controls the pressure relief rate and temperature, and prepares low shrinkage and high rebound supercritical polyurethane foamed beads.
It effectively improves the skeleton strength and resilience of foamed beads, reduces the shrinkage rate, reduces the impact of carbon dioxide diffusion on the structure, avoids shriveling and appearance problems, and improves the overall performance of the product.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane production, in particular to low-shrinkage, high-resilience supercritical polyurethane foam beads and a preparation method thereof. Background Art
[0002] ETPU, or foamed TPU, is the full name of "high resilience lightweight thermoplastic polyurethane elastomer". It is the most elastic foam particle on the market. ETPU has the advantages of light weight, high elasticity, wear resistance, good low temperature performance, and environmental protection. It is widely used in high-end sports equipment, automobiles, health care and other fields. It greatly improves the comfort of human movement and riding through bionics, and has broad market prospects. At present, supercritical physical foaming process is mostly adopted, and the foaming agent is mainly carbon dioxide and nitrogen. Since supercritical carbon dioxide has a better plasticizing effect on TPU, it is widely used.
[0003] When using carbon dioxide as a foaming agent for supercritical foaming, the ETPU matrix is still in a highly elastic state during the rapid pressure release stage, and the skeleton strength is relatively poor. At the same time, due to the large difference between the carbon dioxide concentration in the ETPU pores and the carbon dioxide concentration in the outside atmosphere, the internal carbon dioxide will diffuse outward quickly, which can easily cause the product to become shrunken and wrinkled on the surface. Patent CN 118546425 A mentions adding a pressure-maintaining aging kettle during the foaming stage. After one foaming is completed, the ETPU is matured in the pressure-maintaining aging kettle. After the ETPU strength reaches the requirements, it is released for drying and packaging. This process greatly extends the entire foaming cycle.
[0004] By increasing the glass transition temperature (Tg) of TPU itself, ETPU can quickly enter the glass state from the highly elastic state after foaming and decompression. The molecular chain segments are frozen, which strengthens the rigidity of the system skeleton and provides better support. The basic structural skeleton can be kept unaffected during carbon dioxide diffusion and pore gas exchange, and the shrinkage rate can be reduced. The resilience of the foamed beads will also be improved. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the purpose of the present invention is to provide a low shrinkage, high resilience supercritical polyurethane foam beads. By introducing a benzene ring structure into the TPU soft segment, the glass transition temperature of TPU itself can be increased, and the polarity of TPU can also be enhanced to maintain the product with better strength.
[0006] Another object of the present invention is to provide a method for preparing low-shrinkage, high-resilience supercritical polyurethane foam beads, by optimizing the synthesis method of polyester polyols, adding dibasic acids separately, adipic acid is first added into a reactor to react with small molecule alcohols, and after the reaction is completed, purified terephthalic acid is added into the reactor to react to make polyester polyols.
[0007] The present invention is achieved by adopting the following technical solutions: The method for preparing the low shrinkage and high resilience supercritical polyurethane foam beads comprises the following steps: (1) Add the dibasic acid, diol and catalyst into the reactor, start stirring, and carry out esterification reaction at 200-210°C for 2h-3h under nitrogen protection, then add refined terephthalic acid, and then carry out ester exchange reaction at 220-230°C and pressure of 0.09-0.1MPa to obtain polyester diol; (2) The antioxidant, catalyst, light stabilizer and the polyester diol obtained in step (1) are mixed and heated to 130-150° C. and mixed thoroughly; the isocyanate is heated to 45-55° C.; the chain extender is heated to 45-55° C.; the heated raw materials are metered and injected into the extruder through a high-speed stirring head, the mixed material is fully reacted and plasticized in the screw, and granulated by an underwater cutting system to obtain a low shrinkage, high resilience supercritical polyurethane; (3) adding low shrinkage, high resilience supercritical polyurethane and water in a mass ratio of 1:2 into an autoclave, then introducing carbon dioxide fluid into the autoclave, raising the temperature to 110-130°C and the pressure to 6-9MPa, and after reaching the set temperature and set pressure, directly releasing the pressure to normal pressure or maintaining the set temperature and set pressure for a certain period of time and then releasing the pressure to normal pressure, and drying to obtain low shrinkage, high resilience supercritical polyurethane foam beads; The catalyst is one of an organic bismuth catalyst, an organic tin catalyst, and a titanate catalyst; The antioxidant is one or more of phenolic antioxidants, amine antioxidants and phosphite antioxidants.
[0008] In the step (1), the amount of purified terephthalic acid is 5-10% of the sum of the mass of the dibasic acid and purified terephthalic acid, and the amount of the dibasic acid is 90-95% of the sum of the mass of the dibasic acid and purified terephthalic acid. The dibasic acid is a mixture of one or two of adipic acid or azelaic acid in any proportion, preferably adipic acid; the diol is a mixture of one or more of ethylene glycol, 1,4-butanediol, 1,2-propylene glycol, and 1,3-propylene glycol in any proportion, preferably 1,4-butanediol.
[0009] In the step (2), the mass percentage of each raw material is: Polyester diol 59%-70% Isocyanate 23%-30% Chain extender 6%-11% Antioxidant 0.1-0.3% Light stabilizer 0.1-0.8% Catalyst 0.008%-0.05%.
[0010] The polyester diols are present in aliphatic groups and aromatic groups, and aliphatic groups and aromatic groups do not exist alternately, as shown below: .
[0011] The isocyanate is one of 4,4'-diphenylmethane diisocyanate and 1,6-hexamethylene diisocyanate (HDI), preferably HDI.
[0012] The chain extender is one or both of 1,2-propylene glycol and 1,4-butanediol (BDO), preferably BDO.
[0013] The phenolic antioxidant is one of 1010 and 1076; the amine antioxidant is 445; and the phosphite antioxidant is one of 168 and 626. The antioxidant is preferably 1010.
[0014] The light stabilizer is one of 944, 622 and LS-144.
[0015] The organic bismuth catalyst is catalyst DY-20, and the organic tin catalyst is T-12. The catalyst is preferably T-12.
[0016] The low shrinkage and high resilience supercritical polyurethane foam beads of the present invention are prepared by the above-mentioned method for preparing the low shrinkage and high resilience supercritical polyurethane foam beads.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention can increase the glass transition temperature of TPU itself by introducing a benzene ring structure into the TPU soft segment, and at the same time enhance the polarity of TPU, thereby maintaining the product with better strength. After foaming and decompression, the high skeleton strength can be quickly restored to ensure that the product can resist the shrinkage stress caused by gas exchange.
[0018] (2) The present invention optimizes the synthesis method of polyester polyols, adds dibasic acids separately, and first puts adipic acid into the reactor to react with small molecule alcohols. After the reaction is completed, purified terephthalic acid is put into the reactor to react, thereby producing polyester polyols. If adipic acid and purified terephthalic acid are repeatedly and cross-existed in the polyol structure, the amount of carbon dioxide dissolved will be significantly reduced, affecting the subsequent pore formation and pore structure, and failing to obtain a better surface effect.
[0019] (3) The present invention optimizes the synthesis method of polyester polyols to obtain polyols with special structures, wherein the aliphatic blocks in the polyols aggregate with each other, thereby providing a better amount of carbon dioxide to be dissolved and promoting foaming. The aromatic blocks aggregate with each other, thereby increasing the glass transition temperature of the product and the strength of the product itself. If the aliphatic blocks and the aromatic blocks appear alternately, the amount of carbon dioxide to be dissolved will be greatly affected, resulting in poor foaming. DETAILED DESCRIPTION
[0020] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0021] Example 1 The low shrinkage, high resilience supercritical polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 69.63% HDI: 23.38% BDO: 6.45% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0022] The molecular weight of the polyester diol is 1000.
[0023] The terephthalic acid component / adipic acid is 5% / 95%. The diol component is 1,4-butanediol.
[0024] Preparation process: Adipic acid, 1,4-butanediol and catalyst T-12 were added to the reactor, stirred evenly, and esterification reaction was carried out at 200°C for 2 hours under nitrogen protection, and then terephthalic acid was added, and then ester exchange reaction was carried out at 220°C and pressure of 0.09MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 135°C and mix them evenly; heat HDI to 55°C; heat BDO to 45°C; inject the heated raw materials into the extruder through a high-speed stirring head after precise measurement, and the mixed materials will be fully reacted and plasticized in the screw, and the final product will be obtained after granulation by the underwater cutting system.
[0025] The product obtained in Example 1 has an outflow temperature of 140°C. 1000g of the product and 2000g of water are added into a 50L reaction foaming kettle at the same time. Then 400g of carbon dioxide fluid is introduced into the autoclave. The temperature is raised to 110°C. The pressure is maintained at 9MPa. The discharge valve of the autoclave is quickly opened to release the pressure quickly to obtain low shrinkage and high resilience supercritical polyurethane foam beads. The pressure release rate is 4MPa / s. Discharge and dry.
[0026] Example 2 The low shrinkage, high resilience supercritical polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 59.67% HDI: 29.28% BDO: 10.51% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0027] The molecular weight of the polyester diol is 1000.
[0028] The ratio of terephthalic acid to adipic acid is 10% to 90%. The diol component is 1,4-butanediol.
[0029] Preparation process: Add adipic acid, 1,4-butanediol and catalyst T-12 into the reactor, stir evenly, carry out esterification reaction at 200°C for 2h under nitrogen protection, then add refined terephthalic acid, and then carry out ester exchange reaction at 230°C and pressure of 0.1MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 145°C and mix them evenly; heat HDI to 45°C; heat BDO to 55°C; inject the heated raw materials into the extruder through a high-speed stirring head after precise metering, and the mixed materials are fully reacted and plasticized in the screw, and the final product is obtained after granulation by the underwater cutting system.
[0030] The product obtained in Example 2 has an outflow temperature of 163°C. 1000g of the product and 2000g of water are added into a 50L reaction foaming kettle at the same time, and then 400g of carbon dioxide fluid is introduced into the autoclave, the temperature is raised to 130°C, the pressure is maintained at 9MPa, the discharge valve of the autoclave is quickly opened, and the pressure is quickly released to obtain low shrinkage and high resilience supercritical polyurethane foam beads, and the pressure release rate is 4MPa / s. Discharge and dry.
[0031] Example 3 The low shrinkage, high resilience supercritical polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 60.67% HDI: 28.82% BDO: 9.97% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0032] The molecular weight of the polyester diol is 1000.
[0033] The terephthalic acid component / adipic acid is 8% / 92%. The diol component is 1,4-butanediol.
[0034] Preparation process: Add adipic acid, 1,4-butanediol and catalyst T-12 into the reactor, stir evenly, carry out esterification reaction at 210°C for 3 hours under nitrogen protection, then add refined terephthalic acid, and then carry out ester exchange reaction at 225°C and pressure of 0.09MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 135°C and mix them evenly; heat HDI to 50°C; heat BDO to 50°C; accurately meter the heated raw materials and inject them into the extruder through a high-speed stirring head. The mixed materials are fully reacted and plasticized in the screw, and the final product is obtained after granulation by the underwater cutting system.
[0035] The product obtained in Example 3 has an outflow temperature of 155°C. 1000g of the product and 2000g of water are added into a 50L reaction foaming kettle at the same time, and then 400g of carbon dioxide fluid is introduced into the autoclave, the temperature is raised to 110°C, the pressure is maintained at 6MPa, the discharge valve of the autoclave is quickly opened, and the pressure is quickly released to obtain low shrinkage and high resilience supercritical polyurethane foam beads, and the pressure release rate is 4MPa / s. Discharge and dry.
[0036] Comparative Example 1 Polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 69.63% HDI: 23.38% BDO: 6.45% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0037] The molecular weight of the polyester diol is 1000.
[0038] The terephthalic acid component / adipic acid is 15% / 85%. The diol component is 1,4-butanediol.
[0039] Preparation process: Add adipic acid, 1,4-butanediol and catalyst T-12 into the reactor, stir evenly, carry out esterification reaction at 205°C for 2.5h under nitrogen protection, then add refined terephthalic acid, and then carry out ester exchange reaction at 230°C and pressure of 0.1MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 135°C and mix them evenly; heat HDI to 55°C; heat BDO to 45°C; inject the heated raw materials into the extruder through a high-speed stirring head after precise measurement, and the mixed materials will be fully reacted and plasticized in the screw, and the final product will be obtained after granulation by the underwater cutting system.
[0040] The product obtained in Comparative Example 1 has an outflow temperature of 140°C. 1000g of the product and 2000g of water are added into a 50L reaction foaming kettle at the same time, and then 400g of carbon dioxide fluid is introduced into the autoclave, the temperature is raised to 110°C, the pressure is maintained at 9MPa, the discharge valve of the autoclave is quickly opened, and the pressure is quickly released to obtain low shrinkage and high resilience supercritical polyurethane foam beads, and the pressure release rate is 4MPa / s. Discharge and dry.
[0041] Comparative Example 2 Polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 59.67% HDI: 29.28% BDO: 10.51% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0042] The molecular weight of the polyester diol is 1000.
[0043] Terephthalic acid / adipic acid is 0% / 100%. The diol component is 1,4-butanediol.
[0044] Preparation process: Add adipic acid, 1,4-butanediol and catalyst T-12 into the reactor, stir evenly, carry out esterification reaction at 200°C under nitrogen protection, and carry out ester exchange reaction at 230°C and pressure of 0.1MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 145°C and mix them evenly; heat HDI to 45°C; heat BDO to 55°C; inject the heated raw materials into the extruder through a high-speed stirring head after precise metering, and the mixed materials are fully reacted and plasticized in the screw, and the final product is obtained after granulation by the underwater cutting system.
[0045] The product obtained in Comparative Example 2 has an outflow temperature of 163°C. 1000g of the above product and 2000g of water are added to a 50L reaction foaming kettle at the same time, and then 400g of carbon dioxide fluid is introduced into the autoclave, the temperature is raised to 130°C, the pressure is maintained at 9MPa, the discharge valve of the autoclave is quickly opened, and the pressure is quickly released to obtain low shrinkage and high resilience supercritical polyurethane foam beads, and the pressure release rate is 4MPa / s. The obtained beads are quickly transferred to a pressure-maintaining autoclave with a carbon dioxide concentration of 50% and a temperature of 30°C for 12 hours, released, and dried.
[0046] Comparative Example 3 Polyurethane foam beads are made of the following raw materials in percentage by mass: Polyester diol: 59.67% HDI: 29.28% BDO: 10.51% 1010: 0.2% 622: 0.3% T-12: 0.04%.
[0047] The molecular weight of the polyester diol is 1000.
[0048] The terephthalic acid component / adipic acid is 0% / 100%. The diol component is 1,4-butanediol.
[0049] Preparation process: Add adipic acid, 1,4-butanediol and catalyst T-12 into the reactor, stir evenly, carry out esterification reaction at 210°C under nitrogen protection, and carry out ester exchange reaction at 230°C and pressure of 0.09MPa to obtain polyester diol; Mix polyester diol, 1010, T-12 and 622 and heat them to 135°C and mix them evenly; heat HDI to 55°C; heat BDO to 45°C; inject the heated raw materials into the extruder through a high-speed stirring head after precise measurement, and the mixed materials will be fully reacted and plasticized in the screw, and the final product will be obtained after granulation by the underwater cutting system.
[0050] The product obtained in Comparative Example 3 has an outflow temperature of 163°C. 1000g of the above product and 2000g of water are added simultaneously into a 50L reaction foaming kettle, and then 400g of carbon dioxide fluid is introduced into the autoclave. The temperature is raised to 130°C, and the pressure is maintained at 6MPa. The discharge valve of the autoclave is quickly opened, and the pressure is quickly released to obtain low shrinkage, high resilience supercritical polyurethane foam beads, and the pressure release rate is 4MPa / s.
[0051] After the beads were placed at room temperature for 2 days, they were tested: the particle detection indicators in the embodiments and comparative examples mainly included particle density and bulk density, ball rebound, and whether the appearance was shrunk.
[0052] The test data of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.
[0053] Table 1 Test data of Examples 1-3 and Comparative Examples 1-3
[0054] From the above test data, it can be seen that as the proportion of pure terephthalic acid added in the dibasic acid increases, the product effect is improved. However, as the content of terephthalic acid increases, the bulk density tends to decrease. This is because the content of pure terephthalic acid is too high, which leads to a decrease in the dissolution of carbon dioxide and poor foaming effect.
Claims
1. A method for preparing low shrinkage and high resilience supercritical polyurethane foam beads, characterized in that: The following steps are involved: (1) Add the dibasic acid, diol and catalyst into the reactor, start stirring, and carry out esterification reaction at 200-210°C for 2h-3h under nitrogen protection, then add refined terephthalic acid, and then carry out ester exchange reaction at 220-230°C and pressure of 0.09-0.1MPa to obtain polyester diol; (2) The antioxidant, catalyst, light stabilizer and the polyester diol obtained in step (1) are mixed and heated to 130-150° C. and mixed thoroughly; the isocyanate is heated to 45-55° C.; the chain extender is heated to 45-55° C.; the heated raw materials are metered and injected into the extruder through a high-speed stirring head, the mixed material is reacted and plasticized in the screw, and granulated by an underwater cutting system to obtain a low shrinkage and high resilience supercritical polyurethane; (3) adding low shrinkage, high resilience supercritical polyurethane and water in a mass ratio of 1:2 into an autoclave, then introducing carbon dioxide fluid into the autoclave, raising the temperature to 110-130°C and the pressure to 6-9MPa, and after reaching the set temperature and set pressure, directly releasing the pressure to normal pressure or maintaining the set temperature and set pressure for a certain period of time and then releasing the pressure to normal pressure, and drying to obtain low shrinkage, high resilience supercritical polyurethane foam beads; The catalyst is one of an organic bismuth catalyst, an organic tin catalyst, and a titanate catalyst; The antioxidant is one or more of phenolic antioxidants, amine antioxidants and phosphite antioxidants.
2. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: In the step (1), the amount of purified terephthalic acid is 5-10% of the sum of the mass of the dibasic acid and purified terephthalic acid, the amount of the dibasic acid is 90-95% of the sum of the mass of the dibasic acid and purified terephthalic acid, the dibasic acid is a mixture of one or two of adipic acid or azelaic acid in any proportion, and the diol is a mixture of one or more of ethylene glycol, 1,4-butanediol, 1,2-propylene glycol, and 1,3-propylene glycol in any proportion.
3. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: In the step (2), the mass percentage of each raw material is: Polyester diol 59%-70% Isocyanate 23%-30% Chain extender 6%-11% Antioxidant 0.1-0.3% Light stabilizer 0.1-0.8% Catalyst 0.008%-0.05%.
4. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: The isocyanate is one of 4,4'-diphenylmethane diisocyanate and 1,6-hexamethylene diisocyanate.
5. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: The chain extender is one or both of 1,2-propylene glycol and 1,4-butanediol.
6. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: The phenolic antioxidant is one of 1010 and 1076; the amine antioxidant is 445; and the phosphite antioxidant is one of 168 and 626.
7. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: The light stabilizer is one of 944, 622 and LS-144.
8. The method for preparing low shrinkage and high resilience supercritical polyurethane foam beads according to claim 1, characterized in that: The organic bismuth catalyst is catalyst DY-20; the organic tin catalyst is T-12.
9. A low shrinkage, high resilience supercritical polyurethane foam beads, characterized in that: The low shrinkage and high resilience supercritical polyurethane foam beads are prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Thermoplastic polyurethane elastomer foamed bead without crease on surface and production process thereof
CN118546425A
Thermoplastic polyurethane elastomer foam bead and preparation method thereof
CN104194030A
Anti-yellowing thermoplastic polyurethane foamed material and production method thereof
CN110183843A
High-damping thermoplastic polyurethane elastomer and preparation method thereof
CN112457467A
Particle foams consisting of an aromatic polyester-polyurethane multi-block copolymer
CN113260649A